Levobupivacaine attenuates lipopolysaccharide‐induced acute lung injury. (20th April 2016) - Guo, Dan; Li, Kehan; Yang, Muqiang; Zhang, Hongjun; Miao, Yafei
Abstract: Levobupivacaine (LB), a kind of local anesthetic, possesses anti‐inflammatory properties. High‐mobility group box 1 (HMGB1), a nuclear DNA‐binding protein, plays a key role in the development of acute lung injury (ALI). The aim of this study was to investigate whether LB attenuates ALI by the inhibition of HMGB1 expression and to investigate the molecular mechanisms. ALI in male rats was induced by an intratracheal instillation of LPS (5 mg/kg), and male rats received mini‐osmotic pumps containing LB 30 min after LPS exposure. A549 alveolar epithelial cells were incubated with LPS in the presence or absence of LB. An enzyme‐linked immunosorbent assay was used to detect the levels of inflammatory cytokines. Western blotting was used to detect the changes in the expression of toll‐like receptor 2/4 (TLR2/4) and the activation of NF‐κB. The results showed that LB significantly protected animals from LPS‐induced ALI as evidenced by a decrease in the ratio of lung wet to dry weight, total cells, neutrophils, macrophages, and myeloperoxidase activity, associated with a reduced lung histological damage. We also found that LB post‐treatment markedly inhibited the release of HMGB1 and other pro‐inflammatory cytokines. Furthermore, LB significantly inhibited LPS‐induced TLR2/4 protein overexpression and NF‐κB activation in the lung tissues and in LPS‐stimulated A549 alveolar epithelial cells in vitro. These data indicate that LB attenuated LPS‐induced ALI by the inhibition of HMGB1 expression in rats. These benefits were associated with the inhibition of TLR2/4‐NF‐κB pathway by LB.